2020
DOI: 10.1063/5.0008237
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of Janus particles under thermal fields: The role of internal mass anisotropy

Abstract: Janus particles (JPs) are a special kind of colloids that incorporate two hemispheres with distinct physical properties. These particles feature a complex phase behavior and they can be propelled with light by heating them anisotropically when one of the hemispheres is metallic. It has been shown that JPs can be oriented by a homogeneous thermal field. We show using multiscale simulations and theory that the internal mass gradient of the JPs can enhance and even reverse the relative orientation of the particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…[24][25][26] Very recently, we demonstrated that the mass anisotropy, an intrinsic property of heterogeneous JNPs, couples with the heat flux to impart a thermophoretic torque on the JNP, and the particles adopt a preferential orientation in the direction of the thermal field. 27 This thermal-orientation e↵ect has been reported at molecular scales, in water and other polar molecules. 28,29 In this work, we investigate JNPs immersed in liquids as a model system to achieve anisotropic heating.…”
Section: Introductionmentioning
confidence: 63%
“…[24][25][26] Very recently, we demonstrated that the mass anisotropy, an intrinsic property of heterogeneous JNPs, couples with the heat flux to impart a thermophoretic torque on the JNP, and the particles adopt a preferential orientation in the direction of the thermal field. 27 This thermal-orientation e↵ect has been reported at molecular scales, in water and other polar molecules. 28,29 In this work, we investigate JNPs immersed in liquids as a model system to achieve anisotropic heating.…”
Section: Introductionmentioning
confidence: 63%
“…Hence, irrespective of the negligible temperature gradient on the gold side, the rotational velocity is sensitive to the thermo-osmotic mobility coefficient , which can thus confidently be inferred from the measurement. Compared to the substantial thermal-conductivity contrast, the role of mass anisotropy, which can lead to similar polarization effects [ 89 91 ], plays presumably a negligible role in our experiments, as the thin gold cap makes the Janus particle only slightly bottom heavy.…”
Section: Resultsmentioning
confidence: 95%
“…Density ratio and total polarization a. Density ratio: Introducing the auxiliary quantities β A,a ≡ p max v A,a λ A,a /[Dρ(0)], Eqs. (26) and (27) evaluated at x = 0 and x → ∞, respectively, yield…”
Section: Vanishing Integralmentioning
confidence: 99%
“…On one hand, physical modelling aimed at a better understanding and characterization of types of activity and propulsion of individual active particles [9][10][11][12][13][14][15][16][17] and their interactions upon mutual encounters [18][19][20], encounters with walls [21,22] or when exposed to external fields [23][24][25][26][27]. On the other hand, a huge body of simulations and theories (e.g., [4,6,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]) has aimed at the emerging collective properties of very large assemblies of active particles.…”
Section: Introductionmentioning
confidence: 99%